2021
DOI: 10.48550/arxiv.2107.07129
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inferring kilonova population properties with a hierarchical Bayesian framework I : Non-detection methodology and single-event analyses

Siddharth R. Mohite,
Priyadarshini Rajkumar,
Shreya Anand
et al.

Abstract: We present nimbus: a hierarchical Bayesian framework to infer the intrinsic luminosity parameters of kilonovae (KNe) associated with gravitational-wave (GW) events, based purely on non-detections. This framework makes use of GW 3-D distance information and electromagnetic upper limits from a given survey for multiple events, and self-consistently accounts for finite sky-coverage and probability of astrophysical origin. The framework is agnostic to the brightness evolution assumed and can account for multiple e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Catching more kilonovae and afterglows by current and future survey projects would expand our knowl-edge about the population properties of these events. Kasliwal et al (2020); Mohite et al (2021) constrained the population properties of kilonovae based on the nondetection of GW-triggered follow-up observations during O3. Although the properties of kilonova and afterglow emissions from BNS and NSBH mergers can be reasonably well predicted, their low luminosities and fast evolution nature compared with supernova emission makes it difficult to detect them using the traditional timedomain survey projects.…”
Section: Introductionmentioning
confidence: 99%
“…Catching more kilonovae and afterglows by current and future survey projects would expand our knowl-edge about the population properties of these events. Kasliwal et al (2020); Mohite et al (2021) constrained the population properties of kilonovae based on the nondetection of GW-triggered follow-up observations during O3. Although the properties of kilonova and afterglow emissions from BNS and NSBH mergers can be reasonably well predicted, their low luminosities and fast evolution nature compared with supernova emission makes it difficult to detect them using the traditional timedomain survey projects.…”
Section: Introductionmentioning
confidence: 99%
“…It is predicted that there should exist kilonova emission diversity due to different mass ratios (e.g., Dietrich & Ujevic 2017), different kinds of merger remnant (e.g., Kasen et al 2015;Fujibayashi et al 2017;Gill et al 2019;Kawaguchi et al 2020Kawaguchi et al , 2021 and potential energy injections into the ejecta (Yu et al 2013;Metzger & Piro 2014;Ma et al 2018). The statistical analysis of kilonova emission in sGRB afterglows revealed that 3 Kasliwal et al (2020) and Mohite et al (2021) combined the results of GW detections and the non-detections of EM counterparts in O3 to constrain the kilonova luminosity function. the kilonova brightness may have a wide range of distribution and hence confirmed that kilonova emission should be diverse (Gompertz et al 2018;Ascenzi et al 2019;Rossi et al 2020;Rastinejad et al 2021).…”
Section: Kilonova Emissionmentioning
confidence: 99%